DIVERSIDADE GENÉTICA DE POPULAÇÕES DE Gossypium barbadense ENCONTRADAS NO PANTANAL SUL-MATO-GROSSENSE - ANDRADE, Isadora Luciano; ARGUELHO, Stefanie Braga Duarte; LEITE, Ariely de Souza; GONÇALVES, Tauan Corrêa; CAMACHO, Marcos Antonio; SANTOS, Deisy Lúcia Cardoso Alexandrino (ANAIS DO ENIC, 2018)
-